Letter (copy) : Medical unit - Tewson, Vincent
041-0171-001 HVT/FC/998. Secretary's. 29th August, 1936. Dr. C. Brook. The Spanish Medical Aid Committee, 24, New Oxford Street, W.C.1. Dear Dr. Brook, MEDICAL UNIT. I am enclosing a Postal Order for 10/- being a donation towards the Medical Unit, together with letters from two persons offering their services. Yours sincerely, Assistant Secretary. Donation. 2 letters. 292/946/41/171